Cancer in the Anal Transition Zone and Ileoanal Pouch following Surgery for Ulcerative Colitis - Miller-Ocuin, Jennifer L.; Ashburn, Jean H. (Clinics in Colon and Rectal Surgery, 2023)
Restorative proctocolectomy with ileal pouch-anal anastomosis remains the gold standard treatment for patients with ulcerative colitis who desire restoration of intestinal continuity. Despite a significant cancer risk reduction after surgical removal of the colon and rectum, dysplasia and cancers of the ileal pouch or anal transition zone still occur and are a risk even if an anal canal mucosectomy is performed. Surgical care and maintenance after ileoanal anastomosis must include consideration of malignant potential along with other commonly monitored variables such as bowel function and quality of life. Cancers and dysplasia of the ileal pouch are rare but sometimes difficult-to-manage sequelae of pouch surgery.
Keywords: ileoanal pouch; anal transition zone; dysplasia; ulcerative colitis; pouch cancer; anal neoplasia